Formation of thin tungsten oxide layers: characterization and exposure to deuterium. (19th January 2016) - Addab, Y; Martin, C; Pardanaud, C; Khayadjian, J; Achkasov, K; Kogut, D; Cartry, G; Giacometti, G; Cabié, M; Gardarein, J L; Roubin, P
Abstract: Thin tungsten oxide layers with thicknesses up to 250 nm have been formed on W surfaces by thermal oxidation following a parabolic growth rate. The reflectance of the layers in the IR range 2.5–16 μ m has been measured showing a decrease with the layer thickness especially at low wavelengths. Raman microscopy and x-ray diffraction show a nanocrystalline WO3 monoclinic structure. Low energy deuterium plasma exposure (11 eV/D + ) has been performed inducing a phase transition, a change in the sample colour and the formation of tungsten bronze (D x WO3 ). Implantation modifies the whole layer suggesting a deep diffusion of deuterium inside the oxide. After exposure, a deuterium release due to the oxidation of D x WO3 under ambient conditions has been evidenced showing a reversible deuterium retention.